EFEKTIVITAS METODE PROBLEM BASED LEARNING PADA MATA KULIAH PENDIDIKAN AGAMA ISLAM DI POLITEKNIK NEGERI UJUNG PANDANG - Khairun Nisa; Nurbaeti (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The Problem Based Learning method is one of the approaches used in the field of education. Islamic religious education which is a component of the curriculum that aims to form an understandingof religious values and principles, so that students can be sensitive to problems that occur, especially in the field of education. This research aims to see how effective the use of PBL method is in learning Islamic Religious education at Ujung Pandang State Polytechnic. This research is in action research conducted on students of the PNUP Electrical Departement. Data was collected through questionnaires and active observation in class discussions. The results showed that the use of the PBL method encourages to play an active role in group collaboration to offer solutions to problems faced through the use of technology that provides ease of information